Ensino do processo de enfermagem: significados percepções docentes na formação do enfermeiro - Trigueiro, Elizabeth Vasconcelos (2013)
The implementation of the nursing process should be experienced by all nurses during their formative years. However, the lack of implementation of the nursing process for care planning during the educational process and the existing disorder in the formation process prompted the following research questions: What is the meaning of teaching the nursing process to the nursing professors? Do nursing professors use strategies and methods that promote critical thinking in their students? The objective of the study was to analyze the meaning that teaching of the nursing process has for the nursing faculty of the bachalaureate nursing course. Qualitative descriptive study conducted with a sample of 30 faculty members that taught nursing care courses in the nursing program of the Federal University of Rio Grande do Norte (UFRN) in Natal, RN. Two instruments were used, a questionaire and an interview guide. The questionnaire was designed to obtain sociodemographic, educational and work information, of faculty activities and of the teaching of nursing care. The guide was composed of five open questions regarding the understanding and perceptions of the nursing process, its utilization in teaching, and the nursing care teaching strategies. Interview data were submitted to content analysis techniques and interpreted according to the principles of Symbolic Interactionism. Six categories related to the analytical themes were identified: the nursing process as the guide for the care actions; clinical rationality; use of the care activities; teaching relevance; teaching barreirs; teaching strategies with focus on the abilities and competencies of the clinical rationale. Faculty perceptions regarding the teaching of the nursing process; nursing care approach in the nurses‟ formation. The study indicates that the participants understand the relevance of the nursing process a work instrument and that the use of this method during the nurses‟ formation enhances the abilities and competencies for critical thinking that is essencial for care. The strategies for teaching of abilities and competencies were identified, however the nursing faculty should use codes, direction and the influence so that the students can Interact and therefore stimulate the use of the nursing process